Hubungan antara Usia, Pendapatan Keluarga dan Keterlambatan Pencarian Pengobatan TB Paru di Banyumas - Madyo Maryoto; Suci Khasanah (Viva Medika, 2021)
ABSTRACT Pulmonary tuberculosis is a pulmonary infectious disease caused by mycobacterium tuberculosis. The big rate of disease transmission is due to the low Case Detection Rate (CDR).The Delay seeking treatment Pulmonary TB was contributes to disease transmission. This study aims to analyze the relationship and family income by searching for information on pulmonary TB patients in Banyumas Regency. The research design in this study used descriptive correlational analitic. The sample in this study were patients undergoing intensive phase TB treatment (the first 2 months) at the Puskesmas in Banyumas Regency with a sample size of 102 people, the sampling technique was purposive sampling. Where the variables include: Age, family income, and information seeking pulmonary TB treatment. The data analysis used in this research is simple logistic regression The results showed that most of the pulmonary TB patients in the Banyumas Regency area were not delay in seeking treatment, about 56 (54.9%). There is a relationship between age, family stage and delay seeking tratment for pulmonary tuberculosis patients in Banyumas Regency. Keywords: Age, Family Income, and Delay in seeking pulmonary TB treatment Delay, Health Seeking Behavior